Combining a Being Imitated Strategy With IBT Improves Basic Joint Attention Behaviors in Young Children With ASD - Spjut Janson, Birgitta; Heimann, Mikael; Koch, Felix-Sebastian (Frontiers in Psychiatry, 2022)
In the present study, we examined how an initial being imitated (BIm) strategy affected the development of initiating joint attention (IJA) among a group of children newly diagnosed with autism spectrum disorder (ASD). One group received three months of BIm followed by 12 months of intensive behavior treatment (IBT) which equaled treatment as usual whereas a second group received IBT for the entire 15-month study period. We utilized two measures of IJA: an eye gaze and a gesture score (point and show). IJA did not change during the first three months of treatment, nor were any significant between-group differences noted. However, at the end of the 15-month-long intervention period, the BIm group used eye gaze significantly more often to initiate joint attention. No significant change was noted for the gesture score. These results suggest that an early implementation of a being imitated strategy might be useful as less resource intensive but beneficial “start-up” intervention when combined with IBT treatment as a follow-up.